1+6.3z=-2.5

Simple and best practice solution for 1+6.3z=-2.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+6.3z=-2.5 equation:


Simplifying
1 + 6.3z = -2.5

Solving
1 + 6.3z = -2.5

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 6.3z = -2.5 + -1

Combine like terms: 1 + -1 = 0
0 + 6.3z = -2.5 + -1
6.3z = -2.5 + -1

Combine like terms: -2.5 + -1 = -3.5
6.3z = -3.5

Divide each side by '6.3'.
z = -0.5555555556

Simplifying
z = -0.5555555556

See similar equations:

| -15+x=-27 | | 5*18+9y=45 | | 3x^2=-8x+128 | | 6x^2-x-36=0 | | 2.33+3.33y=3y-4 | | -300=-15k | | -5(1-3r)=28+4r | | 5+2x=4x-13 | | 4n+6+-2n=2(n+3) | | 5x+9*0=45 | | 1+6.33z=-2.5 | | 0.062=-0.06m-0.01 | | x^2-20=-125 | | 85=-5(2r-7) | | 4(3-2n)=n+66 | | -4m-7(6-2m)=22 | | 5*0+9y=45 | | .33x=1.33 | | 8y-12-4y+9=0 | | 8y+7=4y-29 | | 9(4-2x)=3(2-6x) | | 15x^2-50x=0 | | 5x-4x=-6+3 | | 0.60x+0.30(70)=0.30(148) | | h/3+h/6=1 | | 7y-20=-2y-47 | | 9=-4.3 | | -6+6n=6(10-10n) | | 3m+8=m+18 | | 36p+4j=33 | | 3x^4+21x^3-36x^2+3=0 | | 2g+4h=47 |

Equations solver categories